Sāk vitt ok vītt of verǫld hverja (audio performance) - Koutsomichalis, Marinos (My University, 2021)
Audio excerpts from the Sāk vitt ok vītt of verǫld hverja project, pivoting on a multi-level exploration of the North Nordic landscape and the artist’s own personal (un)makings of, and creative responses to, it, in terms of photography, video/audio recordings of various acoustic, electromagnetic, geophysical, and anthropological phenomena, text, stones, seafood, and scientific sonification/visualization of data concerning energy consumption, weather change, seismic activity, fish migration, and spatial distribution of marine population. Featured audio excerpts concern Faroe Islands harbour ambience, underwater recordings of boat engines and whale vocalizations in Greenland Sea, geophysical activity from Icelandic geysers, and data sonifications related with CO2 savings due to geothermal energy production in Iceland.
Keywords: North Nordic landscape